Hubungan Religiusitas dan Grit Dengan Subjective Well-Being Pada Mahasiswa Psikologi - Khilwa Khabibah; Aura Shandra Ashary; Shania Putri Kishani; Lucky Purwantini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The transition to college life often requires students to face various challenges and significant changes in their lives. Individuals who have a high level of subjective well-being tend to have the ability to assess life events in a more positive way. This study aims to analyze the relationship between religiosity and grit with subjective well-being in Psychology students at Universitas Islam 45 Bekasi. This study used a quantitative method involving 134 respondents who were determined using a non-probability sampling technique with a consecutive sampling method. Data collection was carried out using three psychological scales, namely the religiosity scale, the grit scale, and the subjective well-being scale, and the data analysis techniques applied included assumption tests using normality and linearity tests, as well as hypothesis tests using correlation tests and multiple linear regression analysis. The results showed that there was a significant positive relationship between religiosity and subjective well-being (r = 0.546, p <0.005), as well as between grit and subjective well-being (r = 0.738, p <0.005). Multiple linear regression analysis revealed that religiosity and grit together could predict 57.6% of the variance in subjective well-being (R2 = 0.576), (F(2,121) = 89.037), (p < 0.001), while the remaining 42.4% was influenced by other factors.